SYMBOLISM OF HOLY GRAIL IN ARTHURIAN LEGEND: A Semiotics-Structuralism Study of Displacing of Meaning in The Cross & the Grail Poem Written by Lucy Larcom - Yuli Suhartati, - (2008)
This paper puts the emphasis on symbolism of Holy Grail in the poem of The Cross and the Grail by Lucy Larcom with the purpose to find the type of unidirectional expression, the representation of Holy Grail, and the context Holy Grail makes sense in the poem. This paper used a Semiotics-Structuralism analysis, a theory developed by Michael Riffaterre in Semiotics of Poetry (1978). The analysis used two basic elements of analysis: unidirectional expression as well heuristic and hermeneutic (retroactive) reading. Before the analysis, firstly the writer collected the word elements, one of poetical elements in a poem, such as: diction, imagery, and figures of speech in the poem. The significance of The Cross and the Grail is produced from its unidirectional expression; while heuristic and hermeneutic (retroactive) reading analyzed the poem, verse by verse thoroughly. The writer found that Holy Grail in the poem has displacing of meaning from "a cup" used by Jesus Christ in the Last Supper and also used by Joseph of Arimathea to collect the crucified Christ's blood to "a symbol of salvation." The concept of salvation occurs from two circumstances, they are the Last Supper and the crucifixion of The Christ. The concept of "salvation" behind the Holy Grail symbol makes sense in the context of "Christian theology" (the Cross).